Genetic studies on production and reproduction traits of Ongole cattle at organized farms - KUMAR, ASHWANI; SINGH, UMESH; SINGH, RAJBIR; VINOO, R (The Indian Journal of Animal Sciences, 2016)
The study was undertaken to assess the genetic and non genetic factors affecting the productive and reproductive performance of Ongole cattle. Record (3,070) of calf weight and lactation records (2,900) of 729 Ongole cows, maintained at livestock farms (LRS, Lam, Guntur; LRS, Mahanandi; GCBF, Chadalwada; and GLF, Chintaldevi) in Andhra Pradesh, daughter of 67 bulls during 25 years from 1985 to 2009 were used in the analysis. The male calves were heavier than female calves. Low heritability estimated for lactation milk yield and reproductive traits indicated that there is less additive genetic variance in these traits and individual selection will not be helpful for improving them. Also, high genetic correlation between lactation milk yield and peak yield indicated that selection for peak yield may bring reasonable genetic improvement in milk yield of Ongole cows. The results also revealed there is a further scope for improvement in milk production and reproductive performance of the animals through better feeding and management practices.